2008
DOI: 10.1152/ajpheart.01128.2007
|View full text |Cite
|
Sign up to set email alerts
|

Progressive nature of chronic mitral regurgitation and the role of tissue Doppler-derived indexes

Abstract: Progressive nature of chronic mitral regurgitation and the role of tissue Doppler-derived indexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…Under these experimental conditions these indices do not allow detection of changes in LV function during the very early stage of the disease, and this is consistent with recent findings 23. Accordingly, a correlation analysis between changes in strain and changes in PRSW, EF or Tau, did not show any closer association between the parameters.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Under these experimental conditions these indices do not allow detection of changes in LV function during the very early stage of the disease, and this is consistent with recent findings 23. Accordingly, a correlation analysis between changes in strain and changes in PRSW, EF or Tau, did not show any closer association between the parameters.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, Marciniak et al22 proposed that, if corrected for LV geometry, tissue Doppler based strain rate could be a sensitive tool to detect subclinical LV dysfunction in asymptomatic patients with severe MR. In a porcine chronic MR model, Neilan et al23 recently showed that tissue Doppler-derived strain and strain rate indices, which initially increased post-MR, decreased to baseline before any detected changes in global LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Although a high LVEF and LVFS was observed in the early stage of MR (within the first 6 -12 wk), decrease in LVEF and LVFS was seen in the late stage. Using a pig model of chronic organic MR, Neilan and colleagues (17) showed that the LV was progressively dilated at 1 and 3 mo induction of MR, but LVEF did not decrease. LV remodeling is associated with systolic impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a reduction in longitudinal s' appears to carry independent prognostic information beyond the impact of LVEF in hypertension [11], heart failure [12] and coronary artery disease [13]. The predictive utility of pulsed Doppler TDI is not restricted to ischaemia; for example, TDI not only falls before any change in LVEF in severe mitral regurgitation [14] but also predicts those patients in whom LVEF will fall following mitral valve replacement [15].…”
Section: Systolic Functionmentioning
confidence: 99%